Glyphosate has low toxicity to citrus plants growing in the field - Gravena, Renan; Victoria Filho, Ricardo; Alves, Pedro Luis C. A.; Mazzafera, Paulo [UNESP]; Gravena, Adriana R. (Agricultural Inst Canada, 2012)
Gravena, R., Filho, R. V., Alves, P. L. C. A., Mazzafera, P. and Gravena, A. R. 2012. Glyphosate has low toxicity to citrus plants growing in the field. Can. J. Plant Sci. 92: 119-127. There has been controversy over whether glyphosate used for weed management in citrus fields causes significant toxicity to citrus plants. Glyphosate may be toxic to non-target plants exposed to accidental application or drift. This work evaluated glyphosate toxicity in plants of Valencia citrus (Citrus sinensis. L. Osbeck) grafted onto 'Rangpur lime' (Citrus limonia L. Osbeck) and citrumelo 'Swingle' (Poncirus trifoliata (L.) Raf x Citrus paradisi Mad) by trunk- or foliar-directed herbicide applications under field conditions. In the first experiment, glyphosate was sprayed at rates of 0, 90, 180, 260, 540, 1080 and 2160 g a.e. ha(-1) directly on the trunk to a height of 5 cm above the grafting region. In the second experiment, glyphosate was sprayed on the plant canopies at rates of 0, 0.036, 0.36, 3.6, 36, 360 and 720 g a.e. ha(-1). There was no visual damage caused by glyphosate applied directly to the trunk, but the plants were affected by glyphosate sprayed directly on the canopies at rates over 360 g a.e. ha(-1). The main symptom was observed in the new shoots formed after the application, indicating an effect on meristems. Little or no effect was observed in mature leaves. Eight days after application the levels of shikimate, total free amino acids and total phenolic compounds were unaffected. All plants affected by glyphosate recovered between 6 and 12 mo after the treatments. Therefore, despite some transient symptoms Valencia citrus grafted onto 'Rangpur lime' and citrumelo 'Swingle' were tolerant to glyphosate.
Keywords: Citrus limonia; Citrus paradisi; Citrus sinensis; Poncirus trifoliate; Amino acids; Growth; shikimate; total free phenolics